Synthesis of pyrrolo[2,1-f][1,2,4]triazin-4(3H)-ones: Rearrangement of pyrrolo[1,2-d][1,3,4]oxadiazines and regioselective intramolecular cyclization of 1,2-biscarbamoyl-substituted 1H-pyrroles - Son, Kkonnip; Park, Seong Jun (Beilstein Journal of Organic Chemistry, 2016)
Pyrrolo[2,1-f][1,2,4]triazin-4(3H)-ones 12 have been easily prepared via nucleophile-induced rearrangement of pyrrolooxadiazines 11 and regioselective intramolecular cyclization of 1,2-biscarbamoyl-substituted 1H-pyrroles 10. In this work, we demonstrated that the described synthetic approaches can be considered to be more facile and practical than previously reported procedures.
Keywords: intramolecular cyclization; pyrrolooxadiazines; pyrrolotriazinone; rearrangement